2021
DOI: 10.1038/s41598-021-81795-3
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant improvement in anti-saccade success rate and postural instability gait difficulty after rTMS treatment for Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a progressive neurological disorder characterised by motor and non-motor deficits. Repetitive transcranial magnetic stimulation (rTMS) over the bilateral primary motor cortex at a high frequency (5 Hz or higher) is reported to be a potential treatment of PD. We aimed to assess the effect of rTMS on eye movement control in patients with PD in their ‘on’ state. We enrolled 14 patients with PD and assessed motor symptoms (Movement Disorder Society-Sponsored Unified Parkinson’s Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Patients with FOG show significantly worse anti-saccade performance, indicating mutually impaired inhibitory control for gait and anti-saccade ( Ewenczyk et al, 2017 ). Okada et al (2021) confirmed that bilateral 10 Hz rTMS to the leg region of the MC improved MDS-UPDRS motor scores and the anti-saccade success rate, both of which require adequate inhibition of the reflexive response. The improvement in the anti-saccade success rate was correlated with that of the postural instability gait difficulty sub-scores of the MDS-UPDRS ( Okada et al, 2021 ).…”
Section: Resultsmentioning
confidence: 52%
“…Patients with FOG show significantly worse anti-saccade performance, indicating mutually impaired inhibitory control for gait and anti-saccade ( Ewenczyk et al, 2017 ). Okada et al (2021) confirmed that bilateral 10 Hz rTMS to the leg region of the MC improved MDS-UPDRS motor scores and the anti-saccade success rate, both of which require adequate inhibition of the reflexive response. The improvement in the anti-saccade success rate was correlated with that of the postural instability gait difficulty sub-scores of the MDS-UPDRS ( Okada et al, 2021 ).…”
Section: Resultsmentioning
confidence: 52%
“…For example, in a pilot study performed by Waldthaler and colleagues (Waldthaler et al 2021a ), 25 PD patients with and without deep brain stimulation (DBS) underwent clinical assessment and an oculometric evaluation over a 1-year period, and found that anti-saccades were correlated with change in MDS-UPDRS III in both groups. Okada and colleagues (Okada et al 2021 ) examined the effects of transcranial magnetic stimulation as a potential treatment of PD, and compared the changes in both eye movement performance and MDS-UPDRS motor scores in 14 PD patients before and after administration of treatment. Despite the small sample, they found that the reduction in anti-saccade error rate was correlated with the sub-scores of postural instability and gait difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in the SC are linked with deficits in the coordination of action and perception (Pretegiani et al, 2019). Notably, a recent study with PD patients show that repetitive transcranial magnetic stimulation in the motor cortex improved anti-saccade success rate and postural instability gait difficulty (Okada et al, 2021). In this line, optogenetic stimulation of the M2 cortex reverts motor dysfunction in a mouse model of PD (Magno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%